Cross-cultural adaptation and inter-rater reliability of the Swedish version of the Chelsea critical care assessment tool (CPAX-Swe) in critically ill patients. Issue 11 (22nd May 2021) - Holdar, Ulrika; Eriksson, Frances; Siesage, Katinka; Corner, Evelyn J.; Ledström, Viktor; Svensson-Raskh, Anna; Kierkegaard, Marie
Abstract: Objectives: To translate and culturally adapt the Chelsea Critical Care Physical Assessment Tool into Swedish and to test the inter-rater reliability of the Swedish version in critically ill patients. Design: This is an observational study. Methods: Translation and cross-cultural adaptation was performed in line with international recommendations, including forward and backward translation and expert round table discussions. The inter-rater reliability of the Chelsea Critical Care Physical Assessment Tool – Swedish was then explored in 50 critically ill adult patients, pragmatically recruited, in a University Hospital clinical setting. Reliability was calculated using intraclass correlation coefficient for aggregated scores and quadratic weighted Cohen's kappa analysis for individual items Results: The expert round table discussion group agreed that the translation was a satisfactory equivalent to the original version and applicable for use within the clinical setting. Reliability of aggregated scores and individual items were very good (intraclass correlation coefficient of 0.97 and quadric weighted kappa values ranging from 0.88 to 0.98). The measurement error for aggregated scores was low, with a standard error of measurement of 1.79, smallest detectable change of 4.95, and limits of agreement of 5.20 and −4.76. The percentage agreement for individual items ranged from 64% to 88%. Conclusion: The Chelsea Critical Care Physical Assessment Tool – Swedish was found applicable and appropriate for assessment of functioning in critically ill patients in an acute setting in Sweden, and it displayed high inter-rater reliability. This implies that the Swedish version can be used as assessment tool within intensive care and acute wards in Sweden. Implications for rehabilitation: There is a lack of validated instruments to test the functional status of critically ill patients in Sweden. The Chelsea Critical Care Physical Assessment Tool is validated and reliable in English. The Chelsea Critical Care Physical Assessment Tool – Swedish is considered reliable for use by physiotherapist in intensive care settings in Sweden. The Swedish version is feasible for use within clinical practice due to its simplicity and strong clinical relevance.